Conductive capacity and tribological properties of several carbon materials in conductive greases. Issue 5 (8th August 2016) - Cao, Zhengfeng; Xia, Yanqiu; Ge, Xiangyu
Abstract : Purpose: The purpose of this paper is to synthesize a new kind of conductive grease which possesses a prominent conductive capacity and good tribological properties. Design/methodology/approach: A two-step method was used to prepare complex lithium-based grease. Ketjen black (KB), acetylene black (AB) and carbon black (CB) were characterized by transmission electron microscope and used as lubricant additives to prepare conductive greases. Conductive capacity was evaluated by a conductivity meter, a surface volume resistivity meter and a circuit resistance meter. Tribological properties were investigated by a reciprocating friction and wear tester (MFT-R4000). The worn surfaces were analyzed by a scanning electron microscope, Raman spectroscopy, energy-dispersive X-ray spectroscopy and X-ray photoelectron spectroscope. Findings: The conductive grease prepared with KB has a prominent conductive capacity at room temperature, 100°C and 150°C. Further, this conductive grease also possesses better tribological properties than AB and KB greases. When the concentration of KB is 1.8 Wt.%, the coefficient of friction and wear width reduced by 11 and 14 per cent, respectively. Originality/value: This work is a new application of nanometer KB as a lubricant additive in grease, which provides a direction for preparing conductive grease. The conductivity and tribology experiments have been carried out though the variation of experiment conductions.